Latihan Berbasis Aplikatif terhadap Peningkatan Ketrampilan Passing Atas Bolavoli (Pengaruh Latihan Berpasangan dan Bermain) Atlet Putra Usia 15-17 Tahun - Ayuningtyas, Aradea Alifah Nabila; Kuncoro, Bagus; Hartini (MAN Insan Cendekia Jambi, 2025)
The purpose of this study was to determine: 1) the difference in the effect of application-based training methods in volleyball on improving overhead passing skills (the effect of pair training and playing) in male athletes aged 15-17 years. 2) Which is better, the effect of pair training and playing on improving overhead passing skills in male athletes aged 15-17 years. The research sample consisted of 30 students. Sampling used a random sampling technique. The research design used a pretest-posttest design. The research data analysis method used a t-test formula calculated using a short formula. The results of the data analysis resulted in the following conclusions: (1) There are differences in the influence of application-based training methods in volleyball on improving overhead passing skills (the influence of pair training and playing) in male athletes aged 15-17 years at the SNJ Jenawi Karanganyar Volleyball Club in 2025. This is proven by the results of the final test calculations for each group, namely thitung = 3.174, which is greater than t tabel = 2.145 with a significance level of 5%. (2) The paired application-based training method has a better effect than the playing application-based training method on improving the overhead passing skills in volleyball games for male athletes aged 15-17 years at the SNJ Jenawi Karanganyar Volleyball Club in 2025. Based on the percentage of results, the improvement in overhead passing skills shows that group 1 (the group that received treatment using the paired application-based training method) was 21.835% > group 2 (the group that received treatment using the playing application-based training method) was 19.688%.